'The nourishing soil of the soul': The role of horticultural therapy in promoting well-being in community-dwelling people with dementia. (October 2017) - Noone, Sarah; Innes, Anthea; Kelly, Fiona; Mayers, Andrew
Two-thirds of people with dementia reside in their own homes; however, support for community-dwelling people with dementia to continue to participate in everyday activities is often lacking, resulting in feelings of depression and isolation among people living with the condition. Engagement in outdoor activities such as gardening can potentially counteract these negative experiences by enabling people with dementia to interact with nature, helping to improve their physical and psychological well-being. Additionally, the collaborative nature of community gardening may encourage the development of a sense of community, thereby enhancing social integration. Despite increasing evidence supporting its therapeutic value for people with dementia in residential care, the benefits of horticultural therapy have yet to be transposed into a community setting. This paper will examine the theoretical support for the application of horticultural therapy in dementia care, before exploring the potential of horticultural therapy as a means of facilitating improved physical and psychological well-being and social integration for people living with dementia within the community.